Update on current treatments for adult acute myeloid leukemia: to treat acute myeloid leukemia intensively or non-intensively? That is the question - Jaramillo Segura, Sonia; Schlenk, Richard Friedrich (Haematologica, 2023)
For several decades, the treatment for acute myeloid leukemia (AML) has been a dichotomous choice between intensive chemotherapy strategies with curative intent and non-intensive options including supportive care. Patients’ age and fitness, as well as comorbidities, primarily influenced this choice. However, the therapeutic armamentarium is evolving, so that there are highly effective and increasingly specific drugs, fitting the mutational profile of a patient’s leukemia. There is now a spectrum of treatment options that are less intense and can be administered in an outpatient setting and to a substantial extent are equally or even more effective than standard intensive therapy. We are, therefore, witnessing a radical change in the treatment landscape of AML. In this review, we examine the current treatment options for patients with AML, considering the molecular spectrum of the disease on the background of patient-related factors.
Gesehen am 16.03.2023